Research on real estate 3D modeling based on integration of physical entity and property entity - Zhang, Jiyi; Yang, Fan; Shi, Zhifeng; Zhang, Chi; Zhou, Liangchen (Frontiers in Earth Science, 2023)
The essence of three-dimensional (3D) real estate modeling is to build a 3D model that meets the requirements of registration business in the information world according to the objective form of real estate objects and relevant legal provisions on real estate registration. It is the application of digital twin technologies in the field of real estate registration. In recent years, scholars have carried out a lot of research and made a number of representative achievements in the fields of 3D real estate modeling. Many countries and regions have started to implement 3D real estate registration. However, different countries have different legal provisions on real estate registration. Compared with other countries and regions in the world that have implemented 3D real estate registration, China's 3D real estate registration is still in the exploratory stage. Although Chinese scholars have done a lot of research from the perspective of 3D real estate registration mode, modeling method, legal framework, etc. Existing researches mainly focus on the geometric modeling of physical entities and ignore the research on integrated modeling of physical entities and legal entities of real estate objects. Meanwhile, existing research results lack the combination with real estate registration practice. This research is one of the core contents of the pilot construction of Xinyi City's two-dimensional (2D) and 3D integrated real estate electronic license registration. Combined with the real estate registration business practice in Xinyi City, this paper has developed a multi-level 3D real estate property rights modeling technology that integrates the physical entity and legal entity of the real estate registration object. Research results were applied to the real estate registration management of Xinyi City, supporting the issuance of the first 2D and 3D integrated real estate registration electronic license in Jiangsu.